Evaluasi pengelolaan limbah bahan berbahaya dan beracun (B3) di Rumah Sakit tipe B Provinsi Riau - Devi Meri Yati; Mubarak Mubarak; Rahman Karnila (SEHATI: Jurnal Kesehatan, 2022)
Hazardous and Toxic Substances (B3) are substances, energy, and or other components which due to their nature, concentration, and or quantity, either directly or indirectly, can pollute and or damage the environment, and or endanger the environment, health, and the survival of humans and other living things. Hospitals need to carry out B3 waste management properly so as not to have an impact on the environment. The purpose of this study was to analyze the volume, characteristics, management, strategies, and economic and social impacts of B3 waste at Arifin Achmad Hospital, Riau Province. This research was conducted at Arifin Achmad Hospital, Riau Province in June-July 2020. This research is a mixed methods research. The data used are primary and secondary data. Data analysis was carried out by descriptive and SWOT analysis techniques. Based on the results of the study, it was found that in 2020, the total amount of waste generated from January - August by Arifin Achmad Hospital, Riau Province was 73,747.5 kg. The highest amount of B3 waste in Arifin Achmad Hospital, Riau Province, is medical waste at 53,237.5 kg, followed by sharp object waste at 7,194 kg. B3 waste management consists of three stages, namely sorting, transporting, and treating waste. Improper waste management can cause inconvenience for patients, health workers, and waste transport officers. There have been no social problems caused by the management of B3 waste and until now there has been no economic value from waste management at Arifin Achmad Hospital, Riau Province.